An agent model of urban economics: Digging into emergence. (November 2015) - Olner, Dan; Evans, Andrew; Heppenstall, Alison
Highlights: We present an agent-based 'monocentric' model of the emergence of urban form. Key conditions for spatial equilibrium are two cost types: distance and proximity. A distributed market is used; this is more suitable to spatial market problems. A density cost is used to show the role of externalities and proximity cost. Emergence should be demoted from end-goal or explanation of agent models to a tool. Abstract: This paper presents an agent-based 'monocentric' model: assuming only a fixed location for firms, outcomes closely parallel those found in classical urban economic models, but emerge through 'bottom-up' interaction in an agent-based model. Agents make buying and movement decisions based on a set of simple costs they face from their current location. These spatial costs are reduced to two types: the costs of moving people and goods across geographical distances and the costs (and benefits) of 'being here' (the effects of being at a particular location such as land costs, amenities or disamenities). Two approaches to land cost are compared: landlords and a 'density cost' proxy. Emergent equilibrium outcomes are found to depend on the interaction of externalities and time. These findings are produced by looking at how agents react to changing four types of cost, two spatial and two non-spatial: commuting, wage, good cost and good delivery. The models explore equilibrium outcomes, the effect of changing costs and the impact of heterogeneous agents, before focusing in on one example to find the source of emergence in the externalities of agent choice. The paper finishes by emphasising the importance of thinking about emergence as a tool, not an end in itself.